118 Multiparametric Cardiovascular Magnetic Resonance Surveillance of Acute Cardiac Allograft Rejection and Characterisation of Transplantation-associated Myocardial Injury. (31st May 2014) - Miller, Christopher; Naish, Josephine; Shaw, Steven; Yonan, Nizar; Williams, Simon; Clark, David; Bishop, Paul; Ainslie, Mark; Borg, Alex; Coutts, Glyn; Parker, Geoffrey; Ray, Simon; et al.
Abstract : Background: Acute cardiac allograft rejection (ACAR) affects approximately 20% of patients in the first year post-transplantation, represents a leading cause of death during this period and confers higher mortality in patients surviving beyond the first year. Clinical features of ACAR are unreliable, therefore serial surveillance endomyocardial biopsies are performed in order to detect ACAR at an early stage. However the procedure is invasive, is associated with uncommon but significant complications and expensive, factors which prevent more frequent monitoring thus limiting optimal immunosuppression titration. This study aimed to prospectively and longitudinally evaluate the performance of multiparametric cardiovascular magnetic resonance (CMR) for detecting and monitoring ACAR in the early phase post-transplant, and characterise graft recovery following transplantation. Methods: All patients receiving a heart transplant at a single UK centre over a 25 month period of were prospectively approached within one month of transplantation. Multiparametric CMR was prospectively performed on the same day as biopsy on four separate occasions (to coincide with biopsies scheduled at 6 weeks, 10 weeks, 15 weeks and 20 weeks post-transplant). CMR included assessment of global and regional ventricular function (LV volumetrics, mass, ejection fraction, circumferential strain and strain rate, torsion (circumferential-longitudinal shear)), myocardial tissue characterisation (T1 mapping, T2 mapping, extracellular volume, LGE) and pixel-wise absolute myocardial blood flow quantification. CMR parameters were compared with biopsy findings. As is standard, >grade 2R ACAR was considered significant. Results: 88 CMR-matched biopsies were performed in 22 patients. Eight (9%) biopsies in 5 patients demonstrated significant ACAR. Significant ACAR was associated with a reduction in circumferential strain (-12.7 ± 2.5% vs. -13.7 ± 3.6%, p = 0.047) but there was considerable overlap between groups (Figure 1 ). Whilst trends were observed between ACAR and CMR markers of oedema, differences were not significant (Figure 1 ). Significant improvements were seen in markers of graft structure and contractility, oedema and microvascular function over the period studied, although few parameters normalised (Figure 2 ). Primary graft dysfunction (a clinical syndrome defined as severe ventricular dysfunction developing immediately after transplantation and responsible for up to 40% of deaths in the early post-operative period), was associated with markedly abnormal markers of oedema and contractile function. Conclusions: This study provides novel insight into the myocardial injury associated with transplantation and primary graft dysfunction, and its recovery, however multiparametric CMR was not able to accurately detect ACAR during the early phase post-transplantation.